A Study of the Reactions of Transient Silylenes with Carbonyl Compounds in Solution - Son, Michael (My University, 2019)
The reactions of the transient silylenes SiMe2, SiPh2, and SiMes2 with enolizable and non-enolizable carbonyl compounds have been studied in solution by steady state and laser flash photolysis methods. These reactions have been shown to involve the initial formation of a silacarbonyl ylide intermediate, which has been detected directly in several cases and found to exhibit a broad absorption band in the λmax ≈ 500 – 650 nm range in solution. The ensuing chemistry of these intermediates depends on the nature of the carbonyl compound. The reactions of silylenes with enolizable carbonyl compounds generate ene-adducts formed via H-migration in the silacarbonyl ylide. Kinetic isotope effects were investigated in the reactions of the three silylenes with acetone(-d6) and camphor(-d2). The results show an isotope effect for camphor, which indicates the H-migration step is the rate-determining step in the reaction. The effects of ring strain in the carbonyl compound were investigated with dicyclopropyl ketone, relative to diisopropyl ketone. The introduction of ring strain causes a systematic decrease in the rate constants. On the other hand, the reactions of silylenes with non-enolizable carbonyl compounds proceed via cycloaddition. The reactions of SiMes2 with 2,2,5,5-tetramethylcyclopentanone and SiPh2 with 2-adamantanone afford [1+2] and [1+2+2]-cycloadducts, respectively. The kinetic behavior of the silylene and silacarbonyl ylide of these systems are reflective of their corresponding reaction mechanism. However, the kinetic behavior of the silacarbonyl ylides in the reactions of SiMe2 with SiPh2 with 2,2,5,5-tetramethylcyclopentanone and di-tert-butyl ketone are more complex to interpret because a stable cycloadduct is not observed. The trends in the reactivity of the three silylenes, and in some cases the silacarbonyl ylides, with the series of enolizable and non-enolizable carbonyl compounds studied in our group are discussed in this thesis.
Keywords: Silylene